Patterns and Outcomes of Cutaneous Adverse Drug Reactions in a Hospital Based Study - Upama Paudel; S Parajuli; DB Pokhrel (Nepal Journal of Dermatology, Venereology & Leprology)
Introduction : Drug reactions are one of the common reasons for admission in the Dermatological beds. Data on the culprit drugs and patterns of reaction are very scarce in Nepal.